Cross-Sectional Study on the Comparative Assessment of Mandibular Anesthesia (Inferior Alveolar Nerve Blockage) Manual Skills Shaping among Dentists on Plastic and Biomaterial Models - Yuriy Vasil'ev; Ekaterina Diachkova; Hadi Darawsheh; Artem Kashtanov; Ekaterina Molotok; Beatrice Volel; Artem Batov; Olesya Kytko; Rinat Saleev; Gulshat Saleeva; Laysan Saleeva; Irina Smilyk; et al. (MDPI AG, 2022)
Background: Providing regional anesthesia skills shaping remains relevant nowadays. A number of studies show that dentists have difficulties with these working independently. The study aim is the comparative analysis of the results of mandibular anesthesia (IANB) manual-skills shaping among dentists on plastic models and cadavers. Methods: In total, 999 participants were training in the skills of mandibular anesthesia from 2017 to 2021. The participants were divided in a random way into two groups: 700 participants were trained on plastic models, and 299 were trained on the cadaver material. After a lecture on the clinical and anatomical guidelines for IANB, a demonstration of the technique was provided, with subsequent testing of the injection technique. Satisfaction with the aspects of the training was assessed using the Likert scale. Results: the analysis of average values showed that participants from the group in which the manual skills were practiced on cadavers were more satisfied with the main aspects of the training, according to the sum of the main criteria of the modified scale. Conclusions: The important advantages of cadaver educational technology are that the sensations of tissue resistance are identical to natural ones, the individuality of each object, and the possibility of the visual study of the anesthesia technique, by dissection of the needle course and the location of the anesthetic depot.